Consular letter about secret society of the Double Dragon (1901)
This 1901 consular report, authored by the Portuguese Consul in Shanghai and addressed to the Minister and Secretary of State for Foreign Affairs, documents administrative, judicial, and diplomatic activities pertaining to the Portuguese Consulate in Shanghai during the final months of the consul’s tenure. The document, part of the Consular Records (Series A), outlines delays in fulfilling instructions due to exceptional workloads stemming from the consolidation of consular and deanship duties—a responsibility managed separately in other foreign missions, including those of Germany, England, France, and the United States. The author details measures taken to regularise operations, including staff augmentation and extended working hours, while managing urgent legal cases involving theft, bankruptcy, estate settlements, and nationality verification. Diplomatic priorities included negotiations on riverine navigation improvements on the Dongting River, troop withdrawals, arms import restrictions, indemnity administration, and customs representation. The report underscores the symbolic and diplomatic significance of the consulate, noting honours received from foreign consular corps and Chinese authorities, and highlights the absence of formal recognition for the Portuguese representative despite precedents set by other nations. It concludes with a reflection on the prestige associated with the Shanghai post and an appeal for acknowledgment of its importance within Portugal’s diplomatic hierarchy. This document provides critical insight into late Qing-era consular operations, international diplomacy in treaty-port China, and comparative colonial administrative practices.
Keywords: Academic Research; Administrative Activities; Consolidation of Consular Duties; Consular Records Series A; Consular Report; Deanship Responsibilities; Diplomatic Correspondence; Diplomatic Negotiations; Extended Working Hours; Foreign Affairs Ministry; Governmental Authorities; Historical Documentation; Honours Received; Instruction Fulfillment; International Relations; Judicial Proceedings; Legal Case Management; Nationality Verification; Official Correspondence; Portuguese Consulate Shanghai; Portuguese Diplomatic Service; Riverine Navigation Improvements; Staff Augmentation; Theft and Bankruptcy; Transcription; Workload Delays